(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Vitamin K is crucial in blood clotting and bone health, yet its bioavailability is limited. NEs (NE) have emerged as promising delivery systems for fat-soluble vitamins like vitamin K because they enhance solubility, control drug release, prevent enzymatic degradation, and improve therapeutic efficacy. This study investigates a novel, cold-processed, acoustically stable Menaquinon-7 Nanoemulsion (MK-7 NE) derived from both fermented and standard MK-7. Preclinical optimization is essential for understanding potential toxicities and improving safety. A single oral dose of a placebo and MK-7 NE at varying concentrations, based on body weight, was administered to 35 Wistar albino rats, along with a 2 mg/kg dose of a standard MK-7 solution. Plasma MK-7 concentrations were monitored for 72 hours using HPLC analysis, while histopathological examination assessed tissue degradation in the rats' organs. To evaluate acute toxicity, an adult Danio rerio (Zebrafish) model was exposed to a 20 mg/kg concentration of the NE. The results indicated that MK-7 NE supplementation did not cause tissue or organ damage in either model, demonstrating its safety. These findings support the potential of MK-7 NE as an effective and safe formulation for enhancing vitamin K2 bioavailability and therapeutic benefits while minimizing potential risks.